Challenges in Cement Integrity in Geothermal Wells : A Study of Dieng Geothermal Field - Asra, Fauzan Azmi (Journal of Petroleum and Geothermal Technology, 2025)
Cement integrity plays a crucial role in geothermal well construction, ensuring zonal isolation, casing support, and long-term well stability. The Dieng Geothermal Field presents unique challenges in maintaining cement integrity due to extreme reservoir temperatures exceeding 300°C, highly permeable volcanic formations, and the presence of corrosive gases such as CO₂ and H₂S. These conditions can lead to thermal stress, chemical degradation, and loss circulation, all of which compromise cement performance over time. This study examines the key challenges affecting cement integrity in the Dieng Geothermal Field and evaluates potential mitigation strategies. Advanced cement formulations with silica-enhanced additives, acid-resistant materials, and stage cementing techniques are essential in improving cement stability under high-temperature conditions. Additionally, real-time monitoring tools such as cement bond logs (CBL) and ultrasonic imaging technologies are critical for assessing cement integrity and identifying early failure indicators. The findings of this study emphasize the necessity of a tailored cementing approach to address the specific geological and operational challenges of geothermal wells. By implementing optimized cementing techniques and monitoring systems, operators can enhance the longevity and reliability of geothermal wells, ensuring sustainable energy production from the Dieng Geothermal Field.